2019
DOI: 10.1176/appi.ps.201800510
|View full text |Cite
|
Sign up to set email alerts
|

Law Enforcement and Clinician Partnerships: Training of Trainers for CIT Teams in Liberia, West Africa

Abstract: The crisis intervention team (CIT) model was developed in the United States to align law enforcement goals with those of mental health advocates and service users. Liberia is the first low-income country where CIT has been implemented. After preliminary training of law enforcement officers and mental health clinicians by U.S. CIT experts, the program is now entirely implemented by Liberian personnel. In this column, the authors describe topics addressed in the 5-day training-of-trainers process to prepare Libe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…One model to address this is Crisis Intervention Team (CIT) training in which law enforcement, mental health workers, and service users are trained to work together (Compton et al, 2013). Proof-of-concept testing in Liberia has shown that a 40-hour CIT curriculum and ongoing collaboration between law enforcement and mental health is feasible and beneficial (Kohrt et al, 2015c;Boazak et al, 2019Boazak et al, , 2020. Not only do attitudes change, but suicide attempts in police custody and experiences of violence between police and persons with mental illness are decreased.…”
Section: Police Violence and Structural Violencementioning
confidence: 99%
“…One model to address this is Crisis Intervention Team (CIT) training in which law enforcement, mental health workers, and service users are trained to work together (Compton et al, 2013). Proof-of-concept testing in Liberia has shown that a 40-hour CIT curriculum and ongoing collaboration between law enforcement and mental health is feasible and beneficial (Kohrt et al, 2015c;Boazak et al, 2019Boazak et al, , 2020. Not only do attitudes change, but suicide attempts in police custody and experiences of violence between police and persons with mental illness are decreased.…”
Section: Police Violence and Structural Violencementioning
confidence: 99%
“…As of 2016, CIT training in Liberia was administered by a combination of American CIT experts (CIT researcher with a background in psychiatry and a mental health advocate who has administered and developed multiple CIT programs), Liberian mental health clinicians (nurses and physicians' assistants trained to independently diagnose and treat mental illnesses), and Liberian mental health advocates. After the success of the first training program, TCCMHP and LNPA conducted a training of trainers (ToT) program in 2017 in order to ensure sustainability and local ownership of the CIT program (Boazak et al ., 2019). Since the ToT program, CIT has been led solely by Liberian personnel, including law enforcement officers’ mental health clinicians and service users.…”
Section: Methodsmentioning
confidence: 99%
“…Survey instruments were chosen to measure the impact of the Brain Science training on participants' knowledge of neuroscience (MacNabb et al, 2006b) and attitudes toward mental health issues. Scales employed for these attitudes included a version of the Social Distance scale to measure MH stigma in Liberia (Kohrt et al, 2018;Boazak et al, 2019), and a General Perceptions of People with Mental Illness scale (Kohrt and Swaray, 2011), both in Liberian English. The Social Distance scale consisted of nine statements regarding willingness to engage with someone with mental illness and uses a 4 point Likert scale of 1, definitely willing; 2, probably willing; 3, probably unwilling; and 4, definitely unwilling for a range of 9-36.…”
Section: Instrumentsmentioning
confidence: 99%